URGENSI PENGEMBANGAN SOSIAL DAN EMOSI ANAK USIA DINI - Hj Munirah (LP2M IAIN Sultan Amai Gorontalo, 2018)
Early childhood emotional development take place simultaneously with the social development of young children. Even many who assume that the emotional development in early childhood is strongly influenced by their social development despite later developments that emotion influences also to their social development. Early childhood have liked to establish interpersonal relationships with others. Conversely, if a child has poor interpersonal intelligence, he tends not like mingling with other children, he does not like to share, and very possessive (includes ownership) will be toys. Even being aggressive and screaming when he did not get what he wants.